More frequent naps are associated with lower cognitive development in a cohort of 8-38‐month‐old children, during the Covid‐19 pandemic - Teodora Gliga; Alexandra Hendry; Shannon P. Kong; Ben Ewing; Catherine Davies; Michelle McGillion; Nayeli Gonzalez‐Gomez (Wiley, 2023)
Abstract Background How often a child naps, during infancy, is believed to reflect both intrinsic factors, that is, the need of an immature brain to consolidate information soon after it is acquired, and environmental factors. Difficulty accounting for important environmental factors that interfere with a child's sleep needs (e.g., attending daycare) has clouded our ability to understand the role of intrinsic drivers of napping frequency. Methods Here we investigate sleep patterns in association with two measures of cognitive ability, vocabulary size, measured with the Oxford‐Communicative Development Inventory (N = 298) and cognitive executive functions (EF), measured with the Early EF Questionnaire (N = 463), in a cohort of 8-38‐month‐olds. Importantly, because of the social distancing measures imposed during the Covid‐19 Spring 2020 lockdown, in the UK, measures of sleep were taken when children did not access daycare settings. Results We find that children with more frequent but shorter naps than expected for their age had lower concurrent receptive vocabularies, lower cognitive EF and a slower increase in expressive vocabulary from spring to winter 2020, when age, sex, and SES were accounted for. The negative association between vocabulary and frequency of naps became stronger with age. Conclusions These findings suggest that the structure of daytime sleep is an indicator of cognitive development and highlight the importance of considering environmental perturbations and age when investigating developmental correlates of sleep.